The feeding component in rural and peri-urban smallholder pig systems in Uganda - Pezo, Danilo A.; Ouma, Emily A.; Lule, Peter M.; Dione, Michel M.; Lukuyu, Ben A.; Carter, N.; Roesel, Kristina (International Livestock Research Institute, 2014)
In the last 30 years, Uganda has had a massive growth in pig population, from 190,000 in the late 90’s to 3.2 million pigs in 2008, and currently has the highest per capita consumption of pork in East Africa (3.4 kg year). The majority of Uganda’s pig farmers are smallholders (1.2 million households raise pigs), practicing low input/ low output systems. In the three districts of Kamuli, Masaka and Mukono, where the study was carried out, results of focus group discussions conducted in 35 villages showed that regardless of the setting, whether rural or peri-urban, the smallholder pig production systems are typical crop-livestock system, with high dependence on crop residues, i.e. sweet potato vines, cassava leaves, yam leaves, and Amaranth spp. for pig feeding. However, the relative contribution of those crop residues is strongly affected by rainfall seasonality, which in turn influences crop production. The bulk (>95 %) of crop residues used for feeding pigs is produced on farm. Trading of crop residues is minimal hence comprising only <2% hence they can be obtained from farms for free. Women and children are mostly responsible for pig feeding and management, as well as for collecting crop residues for pigs (85.8 and 78.6% of farms in rural and periurban settings, respectively). Kitchen leftovers, including banana peelings, provide 18–20% of the total ration, whereas forages (i.e., Napier grass) represented 20–28 %, and compounded feeds (commercial and home-mixed) 25–27 %, with maize bran as the main ingredient. The main feeding constraints identified by farmers are: dry season fodder shortages (crop residues and forages); risk of parasite infestation through forages, either grazed or cut and carried. In the case of concentrates, constraints include high cost of commercial feeds, price fluctuation of feed ingredients, and poor quality of purchased feeds. There is a need for enhancing knowledge on feeding strategies and fodder conservation among farmers, but also on proper feed formulation for farmers and feed stockists. The implementation of quality control of feeds available in the market is urgently needed.